Origin, pathogenicity, and transmissibility of a human isolated influenza A(H10N3) virus from China - Wenfei Zhu; Lei Yang; Xue Han; Min Tan; Shumei Zou; Xiyan Li; Weijuan Huang; Xiaoxu Zeng; Dayan Wang (Emerging Microbes and Infections)
Subtype H10 viruses are known to infect humans in Africa, Oceania, and Asia. In 2021, 2022, and recently in April 2024, a novel H10N3 subtype avian influenza virus was found cause human infection with severe pneumonia. Herein, we comprehensively studied the phylogenetic evolution and biological characteristics of the newly emerged influenza A(H10N3) virus. We found that the human isolated H10N3 virus was generated in early 2019 in domestic poultry. The viruses bound to salic acid α2, 3 receptors, indicating their insufficient ability to infect humans. Although a low pathogenic avian influenza virus, the human isolated H10N3 virus exhibited robust pathogenicity in both BALB/c and C57BL/6 mice, with MLD50 1000 times higher than a homologous environmental isolate. The human isolated H10N3 also showed respiratory droplet transmissibility in ferrets. Considering the continuous circulation in avian populations and repeated transmission to humans, strengthened surveillance of H10 subtype viruses in poultry should be put into effect.